2022
DOI: 10.3389/fonc.2022.841411
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA in Gastric Cancer: Mechanisms and Clinical Implications for Drug Resistance

Abstract: Gastric cancer (GC) is the third leading cause of cancer-related deaths worldwide, with high recurrence and mortality rate. Chemotherapy, including 5-fluorouracil (5-FU), adriamycin (ADR), vincristine (VCR), paclitaxel (PTX), and platinum drugs, remains one of the fundamental methods of GC treatment and has efficiently improved patients’ prognosis. However, most patients eventually develop resistance to chemotherapeutic agents, leading to the failure of clinical treatment and patients’ death. Recent studies su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 161 publications
0
32
0
Order By: Relevance
“…Beyond the role of piRNAs and piRNA-associated methylation as biomarkers, several studies have put forward their potential role as therapeutic tools 44 , 78 , 109 , 149 just like other non-coding RNAs 150 - 152 . On the basis of the functional characteristics of piRNAs, we offer some thoughts on piRNA as a possible target for cancer therapy as follows.…”
Section: Pirna/piwi Complex-associated Methylation As a Potential The...mentioning
confidence: 99%
“…Beyond the role of piRNAs and piRNA-associated methylation as biomarkers, several studies have put forward their potential role as therapeutic tools 44 , 78 , 109 , 149 just like other non-coding RNAs 150 - 152 . On the basis of the functional characteristics of piRNAs, we offer some thoughts on piRNA as a possible target for cancer therapy as follows.…”
Section: Pirna/piwi Complex-associated Methylation As a Potential The...mentioning
confidence: 99%
“…lncRNAs have emerged as versatile players in gene regulation in multiple biological and physiopathological contexts, particularly cancer [ 79 ]. The number of lncRNAs involved in carcinogenesis and cancer progression is exponentially increasing.…”
Section: Roles Of Main Noncoding Rnas In Cancermentioning
confidence: 99%
“…LncRNAs are non-protein coding RNAs greater than two hundred nucleotides in length that can bind and consequentially inactivate (sponge) microRNAs. Changes in the expression of LncRNAs have been associated with multiple cancers ( 212 ) including oesophageal- ( 213 ), gastric- ( 214 ) and colorectal cancers ( 215 ). The authors found that NR2F2-AS1 is weakly expressed in gastric cancer tissue and in AGS, MGC-803, SGC-7901 and SNU-1 GC cell lines compared to normal cells and expression negatively correlated with poor prognosis and worse overall survival.…”
Section: The Relationship Between Specific Micrornas and Pdcd4 Expres...mentioning
confidence: 99%